Institutional Investors' Mandatory Voting Disclosure - The Proposal of the European Commission against the Background of the U.S. Experience - Schmolke, Klaus Ulrich (European Business Organization Law Review, 2006)
In its Action Plan ‘Modernising Company Law and Enhancing Corporate Governance in the European Union — A Plan to Move Forward’ of 2003, the European Commission proposed a mandatory disclosure of institutional investors’ voting behaviour with regard to their portfolio companies as a medium-term measure. This proposal was evidently inspired by SEC rules mandating voting disclosure of investment companies and investment advisers adopted in the same year. However, the realisation of the Commission’s proposal is far from certain. It has not only met with strong opposition from commentators when it was presented to the public in 2003, but the Commission itself recently launched a consultation process to reassess the necessity and desirability of the medium and long-term proposals of its Action Plan, thereby indicating that it will take the principle of subsidiarity of EC law much more seriously than it has done in the past. At the same time, the UK Government is getting ready to adopt a disclosure rule at national level. This paper examines the US debate on and experience with institutional investors’ mandatory voting disclosure. With the aid of the insights and arguments thereby gathered, it argues that there continues to be a case for a mandatory voting disclosure rule at EC leve
Keywords: disclosure; institutional investors; SEC; Mandatory Voting Disclosure; Offenlegungspflicht; Offenlegung; Modernising Company Law and Enhancing Corporate Governance in the European Union — A Plan to Move Forward; Modernising Company Law